RANCANG BANGUN SORTIR DAN HITUNG LEMBAR KERTAS A4 OTOMATIS MENGGUNAKAN SENSOR LDR DAN APLIKASI BLYNK - Putri Riyanto, Hanna Alifia (Teknik Elektro Universitas Siliwangi, 2021)
The sorter and counting process of sheets paper still manually in several companies. So, in this study designed a tool that can automatically sorter and count paper based of paper quality. Paper is said to be suitable for use when there are no stains on a clean white sheet of paper, and on the other hand, the paper is said to be unfit for use when the paper is stained with ink. In this research, the LDR sensor functions as a sorting sensor, the resistance value received on the paper will be calculated. When the LDR captures a light resistance value less than 75, the paper will be categorized as a good paper quality, and vice versa when the LDR captures a light resistance of more than 75, the paper will be categorized as a dirty paper quality. next process the paper will be pushed to each shelf, this process involves a photodiode as a paper counter. When the paper passes through the photodiode, the process will be counted as one cycle or one paper. Furthermore, the paper will be separated into different racks according to the paper quality using the MG955 servo motor. In the servo motor test, the angular movement is 10Âº for good paper racks and 60Âº for dirty paper racks. After going through the process, the overall results of the paper data will be sent to NodeMCU ESP8266 and displayed on the blynk application.Â Keywords: LDR, Photodioda, Motor Servo, NodeMCU ESP8266.